Detecting Regime Shifts in the Portuguese Continental Shelf Ecosystem Within the Last Three Decades - Szalaj, Dorota; Silva, Alexandra; Ré, Pedro; Cabral, Henrique (Frontiers in Marine Science, 2021)
Marine ecosystems are affected by diverse pressures and consequently may undergo significant changes that can be interpreted as regime shifts. In this study we used integrated trend analysis that combines multivariate statistics and methodologies to identify abrupt changes in time-series, in order to test a hypothesis about the occurrence of regime shifts in the Portuguese Continental Shelf Ecosystem (PCSE). We used two types of data describing ecosystem drivers (fishing mortality and environmental/climatic indices) and ecosystem state (observed and modelled biomass and ecosystem indices). Modelled biomass and ecosystem indices were outputs of Ecopath with Ecosim temporal model parametrised for PSCE between 1986 and 2017. The analyses indicated that the regime shifts in the PCSE have occurred during three periods in the last three decades: “early regime” until the mid-1990s, followed by “transition regime” in-between and “late regime” since the mid-2010s. The detected regime shifts are characterised by changes in the pelagic community that became more dominant when compared to the demersal community and shifted from sardine, the main fishing resource, abundant in the “early regime”, to other less valuable pelagic fishes such as chub mackerel that dominated the “late regime”. The “early regime” was characterised by high catch, a larger proportion of demersal species, and higher diversity while, the “late regime” was represented by lower catch, an increase in higher trophic level predatory fish and lower diversity. Moreover, the “late regime” showed lower resilience and reduced maturity when compared to the “early regime”. Changes described in the ecosystem were probably related to (1) the shift in the north Atlantic environmental conditions that affected small pelagic fish and lower trophic levels groups, (2) reduction in fishing pressure and (3) internal triggers, related to the indirect trophic interactions that might have benefited higher trophic level fish and impacted the pelagic community. In the context of PCSE management, this study highlighted a need to consider the possibility of regime shifts in the management process. For example, regime specific harvest rates and environmental reference points should be considered when an indication of abrupt change in the ecosystem exists.